Wherever there is light : [large type] a novel - Golden, Peter, 1953- (Thorndike Press large print basic series., 2016)
From the author of Comeback Love comes a sweeping, panoramic tale of twentieth-century America, chronicling the decades-long love affair between a Jewish immigrant and the granddaughter of a slave.